PENGEMBANGAN TES DIAGNOSTIK UNTUK MENGIDENTIFIKASI MISKONSEPSI HUKUM ARCHIMEDES KELAS VIII SMP DI KUBU RAYA - Dhiya Ratna Sari; Stepanus Sahala Sitompul; Syukran Mursyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
This study aims to produce a multiple choice diagnostic test on the Archimedes Law to identify misconceptions of junior high school students in Kubu Raya Regency. The method used in this research is Research and Development (R&D). The test development steps used are the Borg and Gall development steps which consist of 7 steps. The test consisted of 30 multiple choice questions accompanied by reasons followed by 28 small-scale test students and 119 students on large-scale test. The characteristics of the diagnostic test used consist of 6 characteristics. The results of the data analysis are appropriate if it is associated with good test characteristics, namely the test is specifically designed to detect misconceptions and developed based on the students' initial conception, the readability level of questions is 4.07 according to junior high school level, has a high validity of 0.75, high reliability of 0.748, and has a level of moderate or low difficulty. From the characteristics of the test, there are 28 questions that can be used. The results of this study are expected to be useful for future researchers as research instruments regarding the Archimedes law